Managing The Future: Foresight In The Knowledge EconomyManaging the Future: Foresight in the Knowledge Economy, edited by TsoukasHaridimos and ShepherdJill. Malden, MA: Blackwell, 2004. - Weick, Karl E. (Academy of Management Review, 2005)
The article reviews the book ?Managing the Future: Foresight in the Knowledge Economy,? edited by Haridimos Tsoukas and Jill Shepherd.